2016
DOI: 10.1515/reveh-2015-0075
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes: a systematic review of available studies on health risk assessment

Abstract: AbstractObjective:This paper primarily aimed to review articles which specifically quantified the risk of electronic cigarette’s (e-cigarette) usage via the health risk assessment (HRA) approach.Methods:Systematic literature searches were conducted using PubMed search engine databases. Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…A 2016 report by the WHO stated that there is not enough research to quantify the relative risk of NVPs over combustible products , and WHO has previously urged countries to restrict the sale, promotion and use of electronic cigarettes . Additionally, some recent reviews have also demonstrated the inconclusive evidence about the health risks associated with NVPs use . Therefore, our data may be indicating that HPs in England (and in the other countries) may be conflicted about the role of NVPs in smoking cessation due to the opposing positions of various NGO and public health organizations.…”
Section: Discussionmentioning
confidence: 78%
“…A 2016 report by the WHO stated that there is not enough research to quantify the relative risk of NVPs over combustible products , and WHO has previously urged countries to restrict the sale, promotion and use of electronic cigarettes . Additionally, some recent reviews have also demonstrated the inconclusive evidence about the health risks associated with NVPs use . Therefore, our data may be indicating that HPs in England (and in the other countries) may be conflicted about the role of NVPs in smoking cessation due to the opposing positions of various NGO and public health organizations.…”
Section: Discussionmentioning
confidence: 78%
“…Reviews have been published on ENDS in general 1021 or on specific topics, including: health effects 2258 ; impact on smoking cessation 29,4043,45,47,48,51,5973 ; product features 22,39,4143,45,47,7477 ; potential to induce dependence 28,45,47,78,79 ; consumer perceptions 26,48,80,81 ; patterns of use 8,26,43,48,51,8290 ; and policies. 8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic.…”
Section: Contextmentioning
confidence: 99%
“…8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic. 11,13,15,16,2228,33,34,36,39,46,48,5358,60,61,66,68,7075,7982,85,86,8890,93,97,100104 The dramatically changing product landscape warrants frequent updates and synthesis of the rapidly growing evidence to inform prudent practice, policy, and regulation. 9,105,106 This comprehensive review presents a current synthesis of empirical studies on ENDS across a broad range of topics.…”
Section: Contextmentioning
confidence: 99%
“…[33,34] Additional information on the potential health effects of the metals in EC can be found in several recent reviews. [33][34][35][36][37] The ability to map individual components and identify multiple elements in each atomizer structure.is a major advantage of SEM/EDS technology. This method also gives information on the relative abundance of each element.…”
Section: Discussionmentioning
confidence: 99%